Long-acting reversible contraceptives use among adolescent girls and young women in high fertility countries in sub-Saharan Africa - Francis Sambah; Richard Gyan Aboagye; Abdul-Aziz Seidu; Charles Lwanga Tengan; Tarif Salihu; Bright Opoku Ahinkorah (BMC, 2022)
Plain language summary The use of long-acting reversible contraceptives can contribute to the reduction of unintended pregnancies. Hence, knowledge of the prevalence and predictors of long-acting reversible contraceptives use among adolescent girls and young women in high fertility countries in sub-Saharan Africa is important in public health. Our study examined the predictors of long-acting reversible contraceptives among adolescent girls and young women in ten high fertility countries in sub-Saharan Africa. A sample of 5854 sexually active adolescent girls and young women were included in the study. The overall prevalence of long-acting reversible contraceptives utilisation was 17.6% in the ten countries, with the lowest of 1.7% in Angola and the highest of 55.8% in Mali. Adolescent girls and young women who were married had a lower likelihood of using long-acting reversible contraceptives than those who were never married. Adolescent girls and young women who wanted no more children had higher odds of long-acting reversible contraceptive use compared to those who wanted more children. Adolescent girls and young women with one to three births, and those with four or more births were more likely to use long-acting reversible contraceptives than those who had no child. To reduce the rates of unplanned pregnancies and induced abortions, there is the need to educate adolescent girls and young women on the advantages of utilising long-acting reversible contraceptives. Additionally, governments, policymakers, and stakeholders in sub-Saharan Africa should raise awareness by executing health promotion measures to enhance the demand for long-acting reversible contraceptives among adolescent girls and young women.